Effect of inherent mineral matter on the co-pyrolysis of highly reactive brown coal and wheat straw. (1st March 2019) - Zhou, Lingmei; Zhang, Guanjun; Reinmöller, Markus; Meyer, Bernd
Graphical abstract: Highlights: Co-pyrolysis of brown coal and biomass are studied by thermogravimetry and HT-XRD. Three different temperature-dependent conversion regimes are recognized. All regimes have offered either positive or negative synergy effects. Synergy effects have resulted from catalytically active minerals in the brown coal. Kinetic parameters are determined using the Coats-Redfern method. Abstract: The co-pyrolysis of coal and biomass is increasingly coming to the fore. For fuel conversion, the effects of artificially added minerals rather than that of inherent mineral minerals are studied in most of the works in the literature. In the present work, the co-pyrolysis behavior of a highly reactive brown coal and wheat straw are investigated up to 1100 °C using a thermogravimetric analyzer and high-temperature X-ray diffraction (HT-XRD). The two methods jointly reveal three different temperature regimes. A negative synergy effect (fewer volatiles) occurs in the cellulose decomposition zone (<400 °C) due to limited heat and mass transfer by the additional coal particles. Meanwhile, positive synergy effects (more volatiles) are observed in an intermediate temperature range between 400 and 700 °C, caused by the catalytically active mineral matter provided by the brown coal. Above 700 °C, the active species from coal and biomass are incorporated in mineral phases and the kinetic limitations lose their influence on the conversion process. HT-XRD and FactSage™ calculations have demonstrated that there are free catalytically active species in these temperature ranges. Finally, the kinetic parameters of the activation energy and pre-exponential factor are determined and compared to the calculated values for the different blends in the various regimes. These parameters agree with the discerned synergy effects and the influence of the mineral matter that is present.